Relational Marketing Model of Education Services Service Marketing Triangle (SMT) in Improving Education Services - Euis Asyiah; Anis Zohriah; Anis Fauzi (South Sulawesi Education Development (SSED), 2024)
Education as an increasingly competitive sector encourages educational institutions to build positive relationships with students, parents, education staff, and donors. This article aims to describe the Relational Marketing Model of the Service Marketing Triangle (SMT) at SMPIT Madinah Al-Hijrah and analyze its contribution to improving educational services. Within the framework of SMT, this article explores how interactions between schools, frontline employees, and education service customers can impact the educational experience and customer satisfaction. Through qualitative research with interviews and surveys with various stakeholders at SMPIT Madinah Al-Hijrah, this article highlights whether the Relational Marketing Model of SMT Education Services at SMPIT Madinah Al-Hijrah can improve education services. The results showed that this model effectively strengthens communication, service quality, and interpersonal interaction in building strong relationships between educational institutions and educational service customers The application of the concept of friend-raising beyond fundraising has also proven successful in attracting new donors through the support of existing donors. In conclusion, this model not only increases the satisfaction of students, parents, and donors but also strengthens loyalty to educational institutions.